PROFESIONALISME PENDIDIK PAUD - Isnaini (Jurnal Sakinah, 2019)
Early age children education is the beginning of higher education levels and becomes the key to make a betterment of the nation’s quality. To achieve the result of children with high quality, among others, it should be supported by professional educators. In carrying out its duties as a teacher must have fours competencies that is pedagogic competance, personal competence, social competence, and professional competence.